A good old text always is a blank for new things. L’Inferno televisivo di Peter Greenaway e Tom Phillips - Giulia Govi (Ricerche di S/Confine, 2021)
A TV Dante – Cantos I-VIII (1989), the TV miniseries co-directed by Peter Greenaway and Tom Phillips, consists in a TV remediation of the first eight cantos from Dante’s Inferno. Taking inspiration from Phillips’ formerly work of Inferno’s illustration and translation (1983), Greenaway unfolds, through video, the metaliterature polysemy of the Italian poet. The essay reflects on Greenaway’s innovative pluricodical paraphrase of Dante’s hell. Within the television frame, thanks to Paintbox graphics, he reconstructs an hypertextual layout which reminds of renowned scholastic editions of the text, but also combine orality, written text, documentary images with original ones, soundtrack and pop-up boxes with extra-diegetic comments. Therefore, the essay analyses some of the series episodes in which different forms of experience merge together.